До проблеми оптимізації системи суб’єктів нагляду і контролю за охороною, захистом, використанням і відтворенням лісів - Колісніченко, С. Ю.; Kolisnichenko, S. Yu. (Право.ua. - 2023. - № 4. - С. 232-237, 2023)
Розкрито загальнотеоретичні питання діяльності суб’єктів нагляду і контролю за охороною, захистом, використанням і відтворенням лісів. Охарактеризовано положення чинного законодавства у досліджуваній сфері, на основі чого виокремлено авторське бачення щодо оптимізації роботи суб’єктів нагляду і контролю за охороною, захистом, використанням і відтворенням лісів. Доведено, що важливим питанням у контексті оптимізації системи суб’єктів нагляду і контролю за охороною, захистом, використанням і відтворенням лісів є участь громадськості у здійсненні зазначеного нагляду та контролю. З метою забезпечення високого рівня законності, об’єктивності та неупередженості контролю і нагляду, необхідно забезпечити широке залучення громадськості до їх здійснення, яке не обмежене лише роботою громадських інспекторів з охорони довкілля.

Attention is focused on the fact that state authorities dealing with management issues in the forestry sector (despite numerous comments by researchers, specialists in environmental and forest control, and the authorities themselves) still combine the functions of control and supervision with economic functions. It is obvious that such a situation does not contribute to achieving a high level of objectivity and impartiality during the implementation of control and supervision measures. For this purpose, it is proposed to speed up the process of creating a state holding company that would deal with issues of economic management in the field of forests and, possibly, unite the existing forestry enterprises in our country into a single integrated system. It has been proven that an important issue in the context of optimizing the system of subjects of supervision and control over the protection, protection, use and reproduction of forests is the participation of the public in the implementation of the said supervision and control. We are convinced that in order to ensure a high level of legality, objectivity and impartiality of control and supervision, it is necessary to ensure broad public involvement in their implementation, which is not limited only to the work of public environmental protection inspectors.

Раскрыты общетеоретические вопросы деятельности субъектов надзора и контроля над охраной, защитой, использованием и воспроизводством лесов. Охарактеризованы положения действующего законодательства в исследуемой сфере, на основе чего выделено авторское видение оптимизации работы субъектов надзора и контроля за охраной, защитой, использованием и воспроизводством лесов. Доказано, что важным вопросом в контексте оптимизации системы субъектов надзора и контроля над охраной, защитой, использованием и воспроизводством лесов является участие общественности в осуществлении указанного надзора и контроля
Keywords: суб’єкти, нагляд, контроль, охорона, захист, відтворення, ліси, оптимізація; subjects; субъекты; нагляд; supervision; надзор; контроль; control; охорона, захист, використання і відтворення лісів; protection, protection, use and reproduction of forests; охрана, защита, использование и воспроизводство лесов; оптимізація; optimization; оптимизация